Responding to observation: how student teachers’ use of their counselor’s notes support their preparation (2005)
Several practices for teacher preparation remain as essential today as they have been for decades. Among them, observation of lessons continues to be highly popular to support and evaluate student teachers’ learning processes. The following pages deal with an experience in which observation was given an alternative perspective in the preparation of future teachers. Sixteen student teachers who constantly responded to their counselor’s observation notes participated in the study. Exploring the participants’ feelings about their counselor’s notes and the nature of their responses to those records were the objectives of the study. At the end, a magnifying glass, a puzzle, a book and a map emerged as valuable metaphors to explain student teachers’ use of this preparation tool. Key words: Pre-service teacher preparation, teaching practice, practicum, supervision, observation, reflective practice, observation instruments, student teachers’ learning Algunas prácticas para la preparación de profesores continúan siendo tan esenciales hoy en día como lo han sido por décadas. Entre éstas, la observación de clases goza de gran popularidad para apoyar y evaluar el proceso de futuros profesores. Las siguientes páginas relatan una experiencia en la cual la observación adquirió un perfil alternativo en la preparación de los futuros docentes. Dieciséis practicantes, quienes constantemente respondieron a las notas de observación, participaron en el estudio tendiente a explorar sus opiniones respecto a las notas del tutor y la naturaleza de sus respuestas a estos registros. Al final, una lupa, un rompecabezas, un libro y un mapa surgieron como metáforas significativas para explicar el uso que los practicantes hicieron de esta herramienta en su preparación. Palabras claves: Preparación de futuros docentes, práctica docente, supervisión, observación, práctica reflexiva, instrumentos de observación, aprendizaje de estudiantes practicantes